Microscopic evaluation of rotatory and handle caries removal on glass ionomer cement/dentin interface - Mauro, Silvio José [UNESP]; Fernandes, Adriana Beatriz Silveira Pinto [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Sundfeld, Renato Herman [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Garbin, Cléa Adas Saliba [UNESP] (Universidade Estadual de Campinas, 2018)
This study evaluated the interface between glass ionomer cement (GIC) and dentin using the conventional and atraumatic restorative treatment (ART) techniques for removal of decayed tissue. Materials and Methods: After preparation of the cavities by the conventional (Group I - GI) and ART (Group II - GII) techniques, the specimens were divided into 3 subgroups according to the GIC used (n=10). The conventional GIC KETAC FILL (3M/ESPE) was used in the groups GI-1 and GII-1, the conventional GIC VIDRION R (SS WHITE) in the groups GI-2 and GII-2, and the modified GIC FUJI II LC (GC Corporation) in the groups GI-3 and GII-3. For the microscopic analysis, the teeth were decalcified in a solution containing equal portions of 50% formic acid and 20% sodium citrate, dehydrated and submitted to paraffin baths. The samples were sectioned (6mm in thickness), stained by the Brown and Brenn method, and evaluated in a light microscope. Results: The microscopic analysis revealed interaction between the material and dentin structure only with the FUJI II LC. In addition, the behavior was superior for the conventional technique in comparison to the ART technique. Conclusion: It was concluded that the technique used for carious dentin removal does not seem to be determinant for the bonding of ionomeric materials to the dental structure, except for the resin-modified GIC in which the formed hybrid layer was higher using the conventional technique.
Keywords: Dental Atraumatic Restorative Treatment; Dental Caries; Glass Ionomer Cements